ANALYSIS OF MARKETING STRATEGIES AND BUSINESS OPPORTUNITIES FOR TRADITIONAL ES KUWUT AMONG THE MILLENNIAL GENERATION - Alyssa Indriani; Dini Nur Hidayah; Aditiya Nugroho; Biyan Imtiyaz Syafi Abdillah; Herdaffa Parama Putra; Hilmy Faiz Abdillah; Abu Naim (RADJA PUBLIKA, 2025)
This study aims to analyze the marketing strategies and business opportunities of the traditional beverage Es Kuwut among the millennial generation. Es Kuwut, as a typical Balinese drink, offers a refreshing taste and great potential to be developed into a trendy beverage business favored by the market. The research method used is descriptive qualitative by collecting data through observations, interviews, and literature reviews related to traditional beverage businesses. The results show that millennials’ interest in traditional drinks is increasing in line with the trend of consuming natural and healthy products. Effective marketing strategies for Es Kuwut businesses include utilizing social media platforms such as Instagram and TikTok, creating attractive packaging designs, and developing innovative flavors tailored to young consumers' preferences. In addition, selecting strategic sales locations, such as areas near campuses or shopping centers, can further enhance the product's appeal. By applying these strategies, Es Kuwut can compete in the modern beverage market while preserving Indonesia’s traditional drinks. This research is expected to serve as a reference for traditional beverage entrepreneurs in developing their businesses in the digital era.